Students’ Perception on the English for Economics Course: An ESP-Based Study - Husnil Mubaraqah; Widya Syafitri; Loli Safitri; Irwandi Irwandi (Austronesian: Journal of Language Science & Literature, 2026)
This study examines students’ perceptions of the English for Economics course at the Faculty of Economics, Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, Indonesia, within the framework of English for Specific Purposes (ESP). The study aims to investigate students’ perceptions regarding the course’s relevance to academic and professional preparation. A quantitative descriptive design was employed using a survey approach. Data were collected from 89 fifth-semester Islamic Economics students through a 41-item closed-ended Likert-scale questionnaire. The instrument was validated using Aiken’s V coefficient and demonstrated strong internal consistency, with a Cronbach’s Alpha value of 0.875. Data were analyzed using descriptive statistical techniques to determine frequency distributions and perception categories. The findings indicate that students generally hold positive perceptions of the course. Approximately 85.4% of respondents perceived the course as relevant, with 79.8% confirming academic relevance and 77.5% acknowledging career relevance. In terms of language skill development, speaking showed the highest perceived improvement (67.4%), followed by listening (65.1%), reading (64.0%), and writing (61.1%). Overall, 84.3% of students reported positive perceptions of the English for Economics course. These results suggest that the course effectively operationalizes ESP principles by aligning instructional objectives with students’ disciplinary and professional needs. However, the unequal distribution of perceived skill development, particularly the comparatively lower improvement in writing, highlights the necessity for more systematic writing instruction and a more balanced pedagogical integration across language skills. In conclusion, the course is pedagogically effective; however, targeted instructional refinement is required to promote comprehensive language competence among economics students.